Implementasi Hypnotherapy dalam Meningkatkan Motivasi - Denok Sunarsi; Ali Maddinsyah; Udin Ahidin; Achmad Setya Roswendi; Dedi Supriadi (Jurnal Pemberdayaan Masyarakat, 2020)
Modern hypnotherapy methods have a greater role to 'open' awareness in knowing the main problem and helping to heal or solve the problem by himself. someone becomes more comfortable with his condition and can accept his condition, so it does not interfere with activities or daily activities. Lack of motivation can reduce self-confidence where every individual, be it an employee, teacher, student, housewife or entertainer desperately needs self-confidence in all fields. The purpose of this community service is to train the participants in applying hypnosis and hypnotherapy and to change the mindset of the participants towards that knowledge. The method used is the presentation of material through seminars and frequently asked questions and simulations both individually and in groups. The result of devotion is that the participants are able to implement hypnosis and hypnosis for the needs of increased motivation, treatment and self-development both for themselves and to help others who experience constraints of confidence and improve performance. The next activity the community service team will conduct hypnoteaching training for teachers and hypomotivation for students.